Pengaruh Indeks Pembangunan Manusia, Ketimpangan Pendapatan, dan Pertumbuhan Ekonomi terhadap Tingkat Kriminalitas di Kabupaten/Kota Provinsi Jambi - Hesmi Susimandri; Junaidi; Jaya Kusuma; Zamzami (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the influence of the human development index, income inequality, and economic growth on crime rates. The independent variables in this study include the human development index, income inequality, and economic growth. While the dependent variable is the crime rate. This study uses secondary data in the form of panel data (time series and cross-section) for the period 2015-2024 with a panel data regression method through the Fixed Effect Model (FEM) approach. The results show that all variables simultaneously have a significant effect on crime. Partially, the human development index has a negative and significant effect, income inequality has no significant effect, while economic growth has a positive and significant effect on crime rates in the regencies/cities of Jambi Province.